2013
DOI: 10.1016/j.amepre.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Cost of a Group Translation of the Diabetes Prevention Program

Abstract: Background Although numerous studies have translated the Diabetes Prevention Program lifestyle intervention into various settings, no study to date has reported a formal cost analysis. Purpose To describe costs associated with the Healthy Living Partnerships to Prevent Diabetes (HELP PD) trial. Design HELP PD was a 24-month RCT testing the impact of a lifestyle weight-loss intervention administered through a diabetes education program and delivered by community health workers (CHWs) on blood glucose and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 14 publications
0
54
0
1
Order By: Relevance
“…All participants signed informed consent and the Institutional Review Board of Wake Forest University Health Sciences approved the trial. Details regarding the HELP PD trial design, participant recruitment, outcomes, and cost have been published elsewhere [9,10,14,15,[22][23][24]. For the purpose of this evaluation, only data from participants in the lifestyle intervention arm is included.…”
Section: Dpp Lifestyle Balance Interventionmentioning
confidence: 99%
“…All participants signed informed consent and the Institutional Review Board of Wake Forest University Health Sciences approved the trial. Details regarding the HELP PD trial design, participant recruitment, outcomes, and cost have been published elsewhere [9,10,14,15,[22][23][24]. For the purpose of this evaluation, only data from participants in the lifestyle intervention arm is included.…”
Section: Dpp Lifestyle Balance Interventionmentioning
confidence: 99%
“…Kahn and Davidson omitted an economic analysis of the Healthy Living Partnerships to Prevent Diabetes (HELP PD) study (2). That analysis provided evidence that the DPP intervention can be delivered by lay community health workers in a group setting for approximately $850 per person over the first 2 years (2).…”
mentioning
confidence: 99%
“…Previous studies have suggested weight-loss programs reduce medical care costs outside interventions. 2,4 If this was also true in this study and the reduction in the medical care costs had been accounted, the program might be more cost-effective. Third, a significant proportion of participants did not complete study assessments.…”
mentioning
confidence: 97%
“…1 The program was estimated to cost $2,204 per kg loss per person, which is somewhat higher than that of similar studies. [2][3][4] For primary care clinics, this study provided a good example of the economic resources needed for delivering a weight-loss program to "a low literacy, inner city" population. A detailed description of their program costs will inform primary care providers of the expected budget impact, as well as potential areas for improving program efficiency.…”
mentioning
confidence: 99%